Implementation of the principles of Good Corporate Governance in public services at the Tirta Pandalungan Water Supply Company Jember - Rifqi Naufal Ario Dimas; Dina Suryawati; Tree Setiawan Pamungkas; Anastasia Murdyastuti (Junal Ilmu Manajemen, 2023)
The implementation of the GCG concept which emphasizes effective and efficient forms of company management by Perumdam Tirta Pandalungan Jember Mangli Branch Office has not been fulfilled due to the company's limited capabilities so that it is necessary to pay attention to see how the implementation of GCG principles is carried out by companies which causes company management to be not effective and efficient. The purpose of this study is to describe the implementation of the principles of Good Corporate Governance in public services at the Regional Public Company Water Drinking Tirta Pandalungan Jember. The method used in this study is qualitative with data collection techniques using observation, interviews, and documentation. Techniques for selecting informants were Purposive and Snowball Sampling and for testing the validity of the data using source triangulation and observation persistence. Data analysis used interactive model qualitative data analysis techniques. The results shown in this study are that the Regional Public Company for Drinking Water Tirta Pandalungan Jember as a rule does not yet have regulations regarding the protection of minority interests because the Regent as the Regional Head Owner of Capital has full authority over company shares, performance measurement in this case DP3 is not based on technology utilization, performance measures for all levels are still based on moral values ​​so that they are not relevant to the company's business goals, the Mangli Branch Office has carried out its social responsibility to the community and the environment through social assistance and greening programs, and conflicts of interest and shifting of responsibility responsibilities between employees shift or lead to helping one another.